Social Work and the gender order: reconfiguration efforts from the Universidad del Valle, Cali-Colombia - Granados-Barco, Adriana; Rodríguez-Pizarro, Alba Nubia (Prospectiva. Revista de Trabajo Social e Intervención Social, 2026)
This article aims to analyze the role of social work in the processes of reconfiguring the gender order at the Universidad del Valle. The gender order, as a social and symbolic structure that organizes the particular way in which higher education institutions operate, is based on social relations and power relations that traverse the bodies, sexualities, and identities of the subjects who inhabit these settings. The article is part of doctoral research that studied the case of this public higher education institution and the configuration and reconfiguration of its gender order between 1980 and 2020. The research was guided by feminist ethnography and historical sociology approaches and built knowledge through document review and interviews with women from the University with academic and activist backgrounds.  In doing so, it identified significant moments in each of the four decades observed that have an impact on the continuous movement of the gender order, allowing us to glimpse the active and persistent presence of the profession and discipline of social work, through its teaching staff, in processes that confront and fracture the androcentric order of the Universidad del Valle. It is a disciplinary space akin to alternative epistemologies, problematizing power structures motivated by the capacity for agency and academic and intellectual influence of female professors who imbue each space with disciplinary meaning.